Simbolismos e motivação no trabalho voluntário : um estudo de caso na associação de voluntários da APAE de Venda Nova do Imigrante - Salazar, Kássia de Aguiar (2014)
The focus of this research is: Understanding the symbolic relationships involving motivation in volunteer work at the Association of Volunteers APAE at Venda Nova do Imigrante city - AVAPAE. To reach the objetive, researchers rely on the relevance of stud